Beyond the School Walls: Keeping Interactive Learning Environments Alive in Confinement for Students in Special Education - Álvarez-Guerrero, Garazi; López de Aguileta, Ane; Racionero-Plaza, Sandra; Flores-Moncada, Lirio Gissela (Frontiers in Psychology, 2021)
The COVID-19 pandemic and the accompanying safety measures, including confinement, has meant an unprecedented challenge for the world population today. However, it has entailed additional difficulties for specific populations, including children and people with disabilities. Being out of school for months has reduced the learning opportunities for many children, such as those with less academic resources at home or with poorer technological connectivity. For students with disabilities, it has entailed losing the quality of the special attention they often need, in addition to a more limited understanding of the situation. In this context, a case study was conducted in a special education classroom of a secondary education school. This class started implementing Dialogic Literary Gatherings with their special education students before the COVID-19 confinement and continued online during the confinement. Qualitative data was collected after a period of implementation of the gatherings showing positive impacts on the participants. The case study shows that interactive learning environments such as the Dialogic Literary Gatherings can provide quality distance learning for students with disabilities, contributing to overcome some of the barriers that the pandemic context creates for the education of these students.